Comparison of AlN vs. SIO2/LiNbO3 Membranes as Sensitive Elements for the SAW-Based Acceleration Measurement: Overcoming the Anisotropy Effects - Sergey Yu. Shevchenko; Denis A. Mikhailenko; Oleg A. Markelov (Sensors, 2020)
We propose the use of aluminum nitride (AlN) membranes acting as sensitive elements for the surface acoustic wave (SAW)-based acceleration measurement. The proposed solution is compared against existing prototypes based on the use of quartz (SiO2)/lithium niobate (LiNbO3) membranes that are characterized by extensive anisotropic properties. Using COMSOL Multiphysics 5.4 computer simulations we show explicitly that sensitive elements based on less anisotropic AlN membranes overcome both the low sensitivity limitations of SiO2 and low temperature stability of LiNbO3. Moreover, AlN membranes exhibit nearly double the robustness against irreversible mechanical deformations when compared against SiO2, which in turn allows for further 1.5-fold sensitivity enhancement over LiNbO3 based sensors. Taking into account their acceptable frequency characteristics, we thus believe that the AlN membranes are a good candidate forsensitive elements especially for high acceleration measurements.